A Scientometric analysis of publications on Artificial Intelligence in India using the Scopus database - Vinodh Kumar, B.; Tamizhchelvan, M. (University of Jaffna, 2022)
This paper focuses on the growth and development of Artificial Intelligence research in terms of publication output in India, as reflected in the Scopus database. During 2012–2021 a total of 21,626 publications were published in the field. The average number of publications published per year was 2162.6, and the highest number of publications, 4,079 were published in 2021. Authors from the Computer Science subject published more publications compared to other subject authors. The most prolific author is Choudhury, T., who contributed 48 publications, followed by Soman, K.P. with 46 publications. Amity University is a highly contributed insti tution with 574 publications, followed by Vellore Institute of Technology with 549 publications; Jadavpur University got the third highest publication position with 385 publications.
Keywords: Artificial Intelligence; Scientometric analysis; Author productivity; Annual growth rate; RGR; DT